The Use of Artificial Intelligence (AI) in Enhancing Teaching and Learning in Private Universities. - Tuntanokij, Sornsak (Chalermkarnchana Academic Journal, 2025)
This research aims to study the impact of Artificial Intelligence (AI) on teaching and learning in private universities using a mixed-methods approach, combining quantitative and qualitative research. Data were collected from faculty members and students through surveys and in-depth interviews. The findings indicate that AI significantly enhances academic performance, with students’ average scores increasing from 72 to 85 after AI implementation. Additionally, both faculty members and students exhibited high levels of satisfaction with AI, with students expressing greater acceptance. These findings align with the Technology Acceptance Model (TAM) and Constructivist Learning Theory. However, concerns remain regarding excessive dependence on AI and ethical considerations. Therefore, it is recommended that guidelines be established for the appropriate use of AI in education.